The embodiment of ‘Chinese strength’: Cultural collectivism in the lyrics of epidemic songs - Zhong, Wenyu; Luo, Mengyu (Perfect Beat, 2021)
This article examines how Chinese songs have incorporated collectivism-oriented cultural values since the outbreak of COVID-19. Such songs are composed to express emotions and cultural values during the global crisis. They are also cultural symbols, sharing not only music but also cultural spirit. This article takes lyrics in Chinese songs, published from February to April 2020, as symbolic texts to analyse the cultural values behind music composing and expression. We identify keywords in song lyrics such as Yi Qing [epidemic], Kang Yi [anti-epidemic] and Xin Guan [COVID-19] via a representative music platform (NetEase Cloud Music) in China. The results show that these lyrics emphasize different levels of collectivism, including eulogizing the nation, advocating unity, and praising national heroes.